Influence of an Equine-Assisted Activities Program on Dementia-Specific Quality of Life. Issue 5 (August 2018) - Fields, Beth; Bruemmer, Jason; Gloeckner, Gene; Wood, Wendy
Institutional facilities face challenges providing experiences to residents with dementia that promote participation in meaningful activities. Guided by the Lived Environment Life Quality Model, this study investigated associations between 9 different activity situations—one an equine-assisted activities program (EAAP)—and positive, negative, and neutral behavioral indicators of quality of life (QoL) in 6 residents with dementia who expressed an interest in horses. Direct observational data were collected for 4 hours twice weekly over 8 weeks. Using χ 2 tests, differences across activity situations were tested. More positive patterns of time use (conversation; χ 2 = 44.3, P < .001) and emotional well-being (pleasure; χ 2 = 21.8, P = .001) were found in EAAP compared to other activity situations. Further, EAAP was the only activity situation associated with all positive QoL indicators. These findings add to our understanding the importance of providing meaningful activities that promote use of abilities and provide environmental support, for enhancing QoL, especially for institutionalized people with dementia.